Surface Motion of Alluvial Valley in Layered Half-Space for Incident Plane P-Waves - 巴振宁 梁建文 (Transactions of Tianjin University, 2011)
The indirect boundary element method （IBEM） is used to study the surface motion of an alluvial valley in layered half-space for incident plane P-waves based on Wolf＇s theory. Firstly, the free field response can be solved by the direct stiffness method, and the scattering wave response is calculated by Green＇s functions of distributed loads acting on inclined lines in a layered half-space. The method is verified by comparing its results with literature and nu- merical analyses are performed by taking the amplification of incident plane P-waves by an alluvial valley in one soil layer resting on bedrock as an example. The results show that there exist distinct differences between the wave ampli- fication by an alluvial valley embedded in layered half-space and that in homogeneous half-space and there is interac- tion between the valley and the soil layer. The amplitudes are relatively large when incident frequencies are close to the soil layer＇s resonant frequencies.